The Clinical Value of the Combined Detection of Systemic Immune-Inflammation Index (SII), Systemic Inflammation Response Index (SIRI), and Prognostic Nutritional Index (PNI) in Early Diagnosis of Gastric Cancer - Zheng J; Zheng L; Wang X; Mao X; Wang Q; Yang Y; Mo D (Journal of Inflammation Research)
Junyu Zheng,1,* Lijun Zheng,2,* Xiao Wang,3 Xuelian Mao,1 Qin Wang,1 Yining Yang,1 Dongping Mo1 1Department of Clinical Laboratory, Jiangsu Cancer Hospital & Nanjing Medical University Affiliated Cancer Hospital & Jiangsu Institute of Cancer Research, Nanjing, People’s Republic of China; 2Department of Clinical Laboratory, Nanjing Lishui District Hospital of Traditional Chinese Medicine, Nanjing, People’s Republic of China; 3Department of CT, Jiangsu Cancer Hospital & Nanjing Medical University Affiliated Cancer Hospital & Jiangsu Institute of Cancer Research, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dongping Mo, Department of Clinical Laboratory, Jiangsu Cancer Hospital & Nanjing Medical University Affiliated Cancer Hospital & Jiangsu Institute of Cancer Research, Baizi Ting No. 42, Nanjing, Jiangsu, 210009, People’s Republic of China, Email moxiaoyubang@163.comObjective: Gastric cancer (GC) is a common malignant tumor of the digestive tract. Accumulating studies suggest that inflammation is linked with the pathogenesis of GC. The study delves into novel hematological inflammatory markers, such as systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), and prognostic nutritional index (PNI), to explore their potential applications in early diagnosis of GC.Methods: From October 2020 and August 2024, 1339 GC patients admitted to our hospital were enrolled in this study. The pre-treatment SII, SIRI, and PNI was calculated from peripheral blood samples. Univariate and multivariate logistic regression analyses were utilized to verify independent risk factors for patients, and constructed the nomograms. The correlation between hematological indicators and tumor-node-metastasis (TNM) stage was assessed through Spearman’s analysis.Results: Eligible patients and healthy controls were grouped by gender. The diagnostic ability of PNI was significantly superior to other indicators to diagnose male GC (area under the curve [AUC]=0.908, 95% CI: 0.892– 0.925) and female GC (AUC=0.890, 95% CI: 0.865– 0.914). Besides, the combination of hematological indicators is more effective in diagnosing GC patients, especially for male patients (AUC=0.916, 95% CI: 0.901– 0.932, sensitivity: 84.98%, specificity: 84.29%). The C-statistic of Nomogram model was 0.917 for males and 0.875 for females. In both male and female cohorts, CEA, SII, and SIRI were positively correlated with TNM stage, while PNI was negatively correlated. The AUC of CEA, SII, SIRI, and PNI combined for the diagnosis in the early stage of male GC patients was 0.897 (95% CI: 0.875– 0.918, sensitivity: 86.57%, specificity: 80.30%) is higher than that of in the advanced stage (AUC: 0.745, 95% CI: 0.710– 0.780, sensitivity: 56.53%, specificity: 82.86%).Conclusion: The combined CEA, SII, PNI, and SIRI could be used as screening biomarkers in diagnosing GC, especially in the early stage of male GC patients.Keywords: gastric cancer, early diagnosis, systemic immune-inflammation index, SII, systemic inflammation response index, SIRI, prognostic nutritional index, PNI